Breaking the Spell: Reconsidering Cognitive and Evolutionary Approaches to Atheism - Szocik, Konrad (Method & theory in the study of religion, 2020)
The scientific study of nonreligion has been described as being ‘under the spell’ of religion because the vast majority of research investigates nonbelief in respect to belief. This has resulted in a number of problematic theories, including the leading cognitive science of religion (CSR) theory that claims that religious belief is innate, and so to be a nonbeliever is to violate cognitive predispositions. This article critically analyzes innateness theories and encourages the development of further theories that incorporate social, adaptive, cultural, evolutionary, and biological factors in addition to cognitive contributors. This article details the roles of adaptive and functional aspects of nonbelief, the influence of credibility enhancing displays (CREDs), and the influence of cultural context on nonbelief as they are not sufficiently explained by CSR theories. It is proposed that future theories study nonreligion in its own right, instead of respective to religion, so that a broader range of unique characteristics can be accounted for without inaccurately and inadequately phrasing theories in terms of naturalness.